A supplementary description of Brisaster iheringi (de Loriol, 1902) (Spatangoida: Schizasteridae) from the Miocene of Patagonia Argentina - Martínez, Sergio Agustín (2017)
New specimens of Schizaster iheringi de Loriol, 1902 from Early Miocene sedimentites (Chenque Formation, Patagonia, Argentina) allowed to improve its original description, providing by the first time details of the apical system and the oral side of test. The species is included into the genus Brisaster, being this the first unquestionable documented reference to the taxon in the Neogene times of Argentina. All previously reported specimens of this species are evaluated, concluding that the stratigraphic range of the genus Brisaster in Patagonia must be restricted to the Early Miocene.